2012
DOI: 10.1111/j.1439-0523.2012.01970.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular dissection of ICRISAT mini core collection of peanut (Arachis hypogaea L.) for high oleic acid

Abstract: With 2 figures and 3 tables Abstract High oleic acid (O) and low linoleic acid (L) make peanut oil ideal for longer storage and better human health. Among the ICRISAT mini core collection accessions, oleic acid ranged from 33.60% to 73.54%. Accessions belonging to ssp. hypogaea had higher oleic acid (54.16%) compared with those of ssp. fastigiata (45.70%). An O : L ratio up to 6.93 was found among ssp. hypogaea. Additional varieties, mutants, germplasm lines and breeding lines had oleic acid within the range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
2
23
1
Order By: Relevance
“…Similarly, in US mini-core collections, 44% (Wang et al, 2011b), 31.6% (Chu et al, 2007) and 41% (Wang et al, 2013b); while in ICRISAT mini-core collections, 49.5% (Mukri et al, 2012) ahFAD2A mutant allele was reported. But, none found having ahFAD2B mutant allele.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Similarly, in US mini-core collections, 44% (Wang et al, 2011b), 31.6% (Chu et al, 2007) and 41% (Wang et al, 2013b); while in ICRISAT mini-core collections, 49.5% (Mukri et al, 2012) ahFAD2A mutant allele was reported. But, none found having ahFAD2B mutant allele.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, in ahFAD2A mutant germplasm lines, the range of mean O/L ratio recorded was 1.11–6.93 with an average of 2.43, whereas, in the non-mutant accessions it was 1.26 with a range of 0.77–2.55 (Mukri et al, 2012). Majority of the ahFAD2A mutant genotypes were found having O/L ratio above 1.5, while non-mutant lines had less than that, with some exceptions (Table 1).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several efforts have been made previously for QTL discovery using sparse genetic maps constructed using SSRs (Huang et al 2015;Varshney et al 2009;Wang et al 2012Wang et al , 2015. Since the genetic base of cultivated peanut is narrow (Belamkar et al 2011;Mukri et al 2012), available SSR markers reported in earlier studies are limited for developing saturated genetic maps. However, single nucleotide polymorphisms (SNPs) are abundant and widely distributed across the genome.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Low O/L hence indicates low oxidative stability (Yanishlieva and Marinova, 2001). On the other hand a high ratio is desirable to enhance oxidative stability and nutritional value (Flagella, Rotunno, Tarantino, Di Caterina, & De Caro, 2002;Mukri et al, 2012). Oyster nut oil had low O/L value of <1 (Table 4).…”
Section: Lipid Health Indices For Oyster Nut Oilmentioning
confidence: 99%